Functional and Morphological Characterization of Small and Large Steroidogenic Luteal Cells From Domestic Cats Before and During Culture - Hryciuk, Michał M.; Braun, Beate C.; Bailey, Liam D.; Jewgenow, Katarina (Frontiers in Endocrinology, 2019)
The current study aimed to isolate, culture and characterize small (SLC) and large (LLC) steroidogenic cells from the corpora lutea (CL) of non-pregnant domestic cats. Isolation of feline SLC was based on an enzymatic digestion of luteal tissue, whereas LLC were obtained by mechanical disruption of CL. To assess function of both cell types, progesterone secretion and mRNA expression of selected genes involved in steroid and prostaglandin synthesis were measured, as well as relative transcript abundance of hormone receptors and anti-oxidative enzymes, before and during culture. The cells were cultured for 3 or 5 days without gonadotropins. Isolated feline SLC and LLC had different sizes (12 ± 3 µm vs. 34 ± 5 µm, respectively), morphologies (amount of lipid droplets) and behaved differently in culture. SLC attached and proliferated or spread quickly, but lost their steroidogenic function during culture (significant decrease in progesterone secretion and expression of steroidogenic genes). The expression of receptors for gonadotropins and prolactin also decreased. Prostaglandin synthase (PTGS2) decreased steadily over time, whereas mRNA expression of PGE2 synthase (PGES) increased. The gene expression of anti-oxidative enzyme glutathione peroxidase 4 (GPX4), also increased during culture, but not of superoxide dismutase 1 (SOD1). In comparison to SLC, LLC did not attach to culture plates, secreted more progesterone per inoculated cells and maintained steroidogenic function during culture. Expression of prostaglandin synthases (PTGS2 and PGES) was almost non-detectable. The gene expression of hormone receptors for prostaglandin F2 alpha (PTGFR), gonadotropins (LHCHR and FSHR), and prolactin (PRLR), as well as of anti-oxidative enzymes (GPX4, SOD1), increased over time. To conclude, we successfully isolated and cultured different types of feline steroidogenic luteal cells and comprehensively characterized both isolated cell types. This knowledge can be used to better understand the CL lifecycle in felines more broadly, and the established cell cultures will provide a foundation for future studies on luteolytic and luteotrophic factors in the domestic cat, and for comparison with other feline species, particularly lynx.